The relationship between paresthesia and the presence of cardiac dysautonomia in patients with post-COVID-19 syndrome: A preliminary observational study - López Galán, Erislandis.; Montoya Pedrón, Arquímedes.; Sánchez Hechavarría, Miguel Enrique.; Muñoz Bustos, Mario Eugenio.; Muñoz Bustos, Gustavo Alejandro. (MDPI, 2023)
Introduction: Post-Coronavirus disease 2019 (Post-COVID-19) syndrome has neurological symptoms related to the dysfunction of the autonomous nerve system. However, a pathogenic relationship between post-COVID-19 syndrome and dysautonomia still remains to be demonstrated. Establishing a pathogenic relationship between paresthesia and the presence of cardiac dysautonomia in patients with post-COVID-19 syndrome is the objective of this study. Participants and Methods: This observational study was carried out in the neurophysiology service wing of the Juan Bruno Zayas Hospital, Santiago de Cuba, in Cuba. The patients were recruited through a post-COVID-19 clinic at the same hospital. A variability study of cardiac frequency and a test of autonomic cardiovascular reflexes was carried out, which is composed of deep breathing, orthostatism, and the Valsalva maneuver. Results: The variability parameters of the cardiac frequency, the expiration–inspiration ratio between deep breaths, and the Valsalva Index showed no statistically significant differences between healthy participants and those with post-COVID-19 syndrome. During the Valsalva maneuver, there was a greater cardiac frequency response in participants with post-COVID-19 syndrome than in healthy subjects. The difference in supine and standing blood pressure was significantly minor in patients with post-COVID-19 syndrome. The logarithm of high frequency (log HF) increased significantly in patients with paresthesia when compared to patients without paresthesia. Conclusions: In the autonomic function tests, no signs of dysautonomia were found in patients with post-COVID-19 syndrome. The presence of paresthesias is associated with differences in cardiac vagal activity, which may suggest that damage to peripheral sensory nerve fibers could be associated with an affectation to autonomic fibres.
Keywords: Dysautonomia; Heart rate variability; Paresthesia; COVID-19 (Enfermedad); Sistema nervioso autónomo